(untitled) (Revista Peruana de Investigación Educativa, 2016)
The massive transit from public to private school in the emerging sector tends to be considered as a response to the low quality of public education. This study argues that the private option would be also responding to the formation of a disposition or habitus that makes that this option be assumed inertial and automatically by families as a realization of an aspirational logic within their path of upward social mobility. Through the exploration of the processes of school choice in a sample of emerging families the study shows how the decision-making processes are mediated by the search for a balance among different criteria which include costs, material conditions of schools, its location and closeness, the pursuit of getting safe places for their children or the student-teacher ratio, among others. In addition, their decisions are strongly influenced by the strategies of identification and social differentiation in the school space. The parents’ strong commitment with the education of their children and the social composition of the families that make up a school are relevant factors for both the identification of those «as one», and the differentiation and exclusion of those who represent «the other», marking a distance from families who send their children to public school or schools of fewer resources. This study seeks to introduce into the debate a better understanding of the process of school choice that goes beyond the search for quality and includes more complex social processes.